2020
DOI: 10.1371/journal.ppat.1008645
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus fumigatus transcription factor RglT is important for gliotoxin biosynthesis and self-protection, and virulence

Abstract: Aspergillus fumigatus is an opportunistic fungal pathogen that secretes an array of immune-modulatory molecules, including secondary metabolites (SMs), which contribute to enhancing fungal fitness and growth within the mammalian host. Gliotoxin (GT) is a SM that interferes with the function and recruitment of innate immune cells, which are essential for eliminating A . fumigatus during invasive infections. We identified a C6 Zn cluster-type transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(60 citation statements)
references
References 72 publications
5
55
0
Order By: Relevance
“…We observed that for TFKO mutants with strongly attenuated ( ∆hapB ), attenuated ( ∆rfeC and ∆ AFUB_014000) or unchanged virulence ( ∆nctA ) in mouse infections, our silkworm model could faithfully predict these phenotypes, even though various mouse models had been used for individual A. fumigatus mutants [ 40 , 41 ]. However, the other four TFKO mutants showed slightly attenuated virulence compared to the WT strain in our silkworm model, which in this case could not reflect the mutant virulence in mouse infections [ 42 , 43 ]. In addition, we also compared seven A. fumigatus TFKO mutants that had been previously generated from other WT progenitors and had been validated in various infection models ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that for TFKO mutants with strongly attenuated ( ∆hapB ), attenuated ( ∆rfeC and ∆ AFUB_014000) or unchanged virulence ( ∆nctA ) in mouse infections, our silkworm model could faithfully predict these phenotypes, even though various mouse models had been used for individual A. fumigatus mutants [ 40 , 41 ]. However, the other four TFKO mutants showed slightly attenuated virulence compared to the WT strain in our silkworm model, which in this case could not reflect the mutant virulence in mouse infections [ 42 , 43 ]. In addition, we also compared seven A. fumigatus TFKO mutants that had been previously generated from other WT progenitors and had been validated in various infection models ( Table S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, while validating the reliability of our optimized silkworm A. fumigatus infection model by comparing the virulence of previously characterized TFKO mutants in silkworm vs. in mouse models, we observed that for mutants with attenuated, strongly attenuated or unchanged virulence, our silkworm model could faithfully recapitulate the results in mouse models, even though various mouse models were used for individual mutants: Different methods of immunosuppression (leukopenic or non-neutropenic) and different routes of infection (intranasal, intratracheal, intravenous or inhalation) accompanied by diverse infectious doses ranging from 10 3 to 10 7 spores/germlings [ 40 , 41 , 44 , 45 , 46 ]. However, for mutants that showed slightly attenuated or increased virulence, our silkworm model was unable to exactly mirror the outcome in mouse models, given that there is no standardized mouse model available [ 42 , 43 , 47 , 48 , 49 , 50 , 51 ]. For example, the ∆gliZ mutant required for gliotoxin biosynthesis showed slightly increased virulence in our silkworm model, while unchanged and attenuated virulence in leukopenic and non-neutropenic mouse models, respectively [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Short reads were submitted to the NCBI's Short Read Archive under the Bioproject SRP154134. Raw reads were aligned to Af293 reference genome using Hisat2 and the differential gene expression quantification was performed as described previously (Ries et al, 2020). Significant differentially expressed genes (DEGs) were selected using q-value <= 0.05 and log2(fold-change) >= 0.6 or log2(fold-change) <= -0.6.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…CrzA:GFP binding sites analysis, the peak calling was performed as described previously (Ries et al, 2020) and the peaks were individually checked using the Integrative genomics viewer (IGV)…”
Section: Chip-sequencingmentioning
confidence: 99%
“…Although previous reports have shown that study of aberrant gene expression and genetic locus association can be helpful in understanding diagnosis and/or treatment of infectious and noninfectious diseases, few reports address IA caused by A. fumigatus (27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%